Cinema e educação : discursos sobre infância e juventude pobre brasileira no filme Pixote, a Lei do Mais Fraco (1981) - Fraga, Cayron Henrique Aparecido (2018)
This research is part of the Research Group for Childhood, Youth and Contemporary Culture (GEIJC), the Postgraduate Program in Education of the Federal University of Mato Grosso, campus Rondonópolis (PPGEdu / UFMT / CUR). Objective to analyze the images of poor Brazilian’s youth and childhood in the film Pixote (BR: 1981). Directed by Hector Babenco, the film is considered a landmark of Brazilian cinema and cinematographic production on Latin American childhood. This research is based on speeches about street children in the 1980s, which, according to Fúlvia Rosemberg's studies, were spread by several actors, including the media, which led to the stigmatization of poor families and children. In this context, one can think how the construction of childhood is also represented in the cinema. The discourses produced by the film industry, most of the time, distribute cultural patterns that are repeated in society. Therefore, it is critical to analyze how cinema is understood as an artistic field and its possible connections and contributions to the educational universe (Duarte). We adopt as a method to develop this research, the studies of Depth Hermeneutics, proposed by John B. Thompson, and which contemplates three phases: 1) socio-historical analysis of the symbolic form analyzed 2) formal or discursive analysis, and 3) interpretation / reinterpretation . The symbolic forms under analysis are some scenes from the film in which they are pertinent to the research theme. The film is analyzed as a symbolic form that contributes to the social construction of poor Brazilian childhood and youth images. Throughout the analysis it was possible to identify the use of a dramatic rhetoric in the narrative about "street children". The film, in attempting to make a complaint about "marginalized childhood," ended up associating poor children with abandonment of their families with crime and dangerousness, reinforcing the idea that such problems and conflicts are synonyms or direct consequences of poverty.